Employment Core Competencies of Chinese Higher Vocational Students: A Systematic Review and Research Agenda - Zheng, Jinhua (Online Journal for TVET Practitioners, 2024)
This study explores the number of publications, major researchers, major research institutions, research hotspots and research trends in this field of study by conducting thematic searches on the Scopus knowledge service platform and bibliometric analyses using CiteSpace.The results indicate that the number of publications on research on structural equation modelling in the area of employment core competencies is increasing, but the total amount of literature is still too small and there are many gaps. Research on the application of structural equation modelling in the field of employment core competencies focuses on topics such as higher education, healthcare, human resources, and behaviour. Future colleges and universities are the main research participants. Considering the lack of richness of current research perspectives, this review also provides suggestions for future research directions in order to strengthen the Chinese higher vocational students’ employment core competency.